INVASI MILITER ISRAEL DI LEBANON SELATAN DALAM SOROTAN HUKUM HUMANITER DAN HAK ASASI MANUSIA - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
World War ll knilled many more civilians than the soldiersÂ As a Hezbollah freedom fighter point out for example, that the only difference between his bombs and Israelli bombs is that he delivers his by truck or hand, while the Israellis deliver theirs Â by bomber or tanks.The Israellis might reply that the onlyreason they (areforced) kill civilians and children is that the Hezbollah people operate among them.Even for the majority who are unlikely to bicome Freedom fighters, the question of justivication is important. We know war is organized killing of other human beings. Virtually everyone is against that. Yet war continous to are binding according to the doctrine of Pacta Sunt Servanda (the treaty must be carried out). The general priciples of law recognized by civilized nations moralty to be considered. As developing International legal system in a now days dynamic wold Political system.International law such as the International Humanitarian law is developing affirmatively in the area of defiling human rights today aggression is outlawed by the U.N Charter and the legimate reason to resort to violence are in self-defencean aspart of a u.n or regional peace keepingefort. There have also been extensive effort to regulate the conduct of warfare. But, haw about Israellis bombing innocent Libanese people and killing children?Â